Safety and efficacy of a feed additive consisting of a tincture derived from the leaves or aerial parts of Thymus serpyllum L. (wild thyme tincture) for use in all animal species (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a tincture from the leaves or aerial parts of Thymus serpyllum L. (wild thyme tincture) when used as a sensory additive in feed and in water for drinking for all animal species. The product is a ■■■■■ solution, with a dry matter content of approximately 1.0%. The product contains on average 0.083% (w/w) total polyphenols (of which 0.0222% are flavonoids). The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the use of wild thyme tincture is safe at the proposed use level of 500 mg/kg complete feed for ornamental fish. For the other species the calculated safe concentrations in complete feed are: 71 mg/kg for chickens for fattening, 106 mg/kg for laying hens, 96 mg/kg for turkeys for fattening, 154 mg/kg for pigs for fattening, 128 mg/kg for piglets, 187 mg/kg for sows, 321 mg/kg for veal calves, 282 mg/kg for cattle for fattening, sheep/goats and horses, 183 mg/kg for dairy cows, 113 mg/kg for rabbits, 322 mg/kg for salmonids, 338 mg/kg for dogs and 282 mg/kg for cats. These conclusions were extrapolated to other physiologically related species. For any other species, the additive is safe at 71 mg/kg complete feed. No safety concerns were identified for the consumer and the environment from the use of the additive in animal feed. Regarding user safety, the additive under assessment should be considered as irritant to skin and eyes, and as a dermal and respiratory sensitiser. Any exposure is considered a risk. Since the leaves of T. serpyllum are recognised to flavour food and their function in feed would be essentially the same as that in food, no further demonstration of efficacy was necessary.